Influence of exam stress on the structure of the circadian heart rate (Experimental biology, 2016)
We analyzed the circadian rhythms of some characteristics of the ECG (heart rate and the number of completed QRS) of students of an university during examinations. Paired t-test daily dynamics of average heart rate and QRS data during examinations and control, regardless of the season showed a significant increase of MESOR (p = 0.019) and a shift of acrophase during exams (p = 0.008). Spectrum of heart rate of students showed high statistical significance for 24-hour rhythm in control (p
Keywords: circadian rhythms; exam stress; students; QRS; heart rate.